Comorbidities related to the COVID-19 severity in adults. Hospital San Vicente de Paul. 2021 - Mónica Echeverría Martínez; Jorge Luis Anaya González; Secundino González Pardo; Juan Francisco Vaca Oña (Medisur)
Foundation: the study of the clinical characteristics of people infected with COVID-19 has shown that factors such as advanced age, male gender and the presence of comorbidities are associated with the clinical variability of this disease. Objective: to determine the comorbidities related to the severity of COVID-19 infections. Methods: research carried out at the San Vicente de Paul Hospital, which includes 200 patients admitted for COVID-19. The collection of information was carried out through the medical records and the degree of severity of COVID-19 was categorized. Pearson's Chi square was used with a significance level of 95%, p≤ 0.005 and the Odds Ratio test for risk estimation. Results: 53% of the patients belong to the male sex and 61.5% presented at least one comorbidity, and arterial hypertension was the most reported (35%); 70% predominated with a serious disease and 2.5% died. Furthermore, chronic obstructive pulmonary disease was associated with an increased risk of developing mild to moderate illness from COVID-19. Conclusions: the study favors monitoring the association between comorbidities as the pandemic progressed and using the information as a prognostic factor to guide early intervention and an appropriate therapeutic approach.